2016
DOI: 10.1016/j.foodhyd.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation properties, release behavior and physicochemical characteristics of water-in-oil-in-water (W/O/W) emulsion stabilized with pectin–pea protein isolate conjugate and Tween 80

Abstract: Water-in-oil-in-water (W 1 /O/W 2) double emulsion is one of the most efficient drug delivery systems. In the double emulsion, the release of a target compound from one phase to another can be controlled by the emulsion composition, emulsification and preparation condition. Tween 80 is mainly used as a high HLB emulsifier; while it may cause many side effects on the human health. The main goal of the present study was to investigate the efficiency of a new hybrid polymer (pectin-pea protein isolate conjugate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 37 publications
3
54
2
1
Order By: Relevance
“…The droplet sizes of the GMS W/O/W emulsions, PGPR W/O/W emulsions, lecithin W/O/W emulsions and Span 80 emulsions are 1.739 mm, 1.584 mm, 1.579 mm, and 1.544 mm, respectively. Tamnak 27 reported that the mean size of W/O/W emulsions prepared with PGPR ranged from 3 to 4 mm, which is different from the values observed in this experiment. This may be due to the fact that in their experiment, pectin-pea protein isolate conjugate, which has a higher molecular weight than Tween 80, was used as the hydrophilic emulsier.…”
Section: Zeta Potentialcontrasting
confidence: 99%
“…The droplet sizes of the GMS W/O/W emulsions, PGPR W/O/W emulsions, lecithin W/O/W emulsions and Span 80 emulsions are 1.739 mm, 1.584 mm, 1.579 mm, and 1.544 mm, respectively. Tamnak 27 reported that the mean size of W/O/W emulsions prepared with PGPR ranged from 3 to 4 mm, which is different from the values observed in this experiment. This may be due to the fact that in their experiment, pectin-pea protein isolate conjugate, which has a higher molecular weight than Tween 80, was used as the hydrophilic emulsier.…”
Section: Zeta Potentialcontrasting
confidence: 99%
“…The entrapment efficiency of tartrazine in double emulsions (EE DE ) was defined as the percentage of tartrazine still in the inner aqueous phase after the preparation of double emulsions and measured using the method of centrifugal ultrafiltration, according to some previous studies (Akhtar, Murray, Afeisume, & Khew, ; Tamnak et al, ). Four hundred microliters of double emulsions was added into ultrafiltration centrifugal filter tube with a molecular weight cut‐off of 30 kDa (Millipore, Burlington, MA) and centrifuged at 10,000 rpm for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It is assumed that this high yield is a consequence of optimized valve design and hydrodynamic flow conditions combining together to limit the intensity of turbulent flow during the 2nd‐stage emulsification. In reality, with standard commercial equipment used to make DE emulsions, many workers choose to operate at intermediate pressures—for example, in the range 3.5 to 5 MPa with the 1‐stage homogenizer EmulsiFlex C5 (Hemar and others ; Giroux and others ) or the 2‐stage APV high‐pressure valve homogenizer (Tamnak and others ). Nonetheless, based on the reports listed in Table , it would seem that significant variability in system composition and processing equipment precludes the deduction of a meaningful correlation between applied homogenization conditions and the yield of encapsulated substances.…”
Section: Preparation Of Double Emulsionsmentioning
confidence: 99%
“…Even before any emulsion processing occurs, protein–polysaccharide interactions may become established during the preparation of the mixed biopolymer ingredients to be used as DE emulsifiers and stabilizers (Dickinson ). Reported examples include the formation of dried covalent conjugates of sodium caseinate with dextran (1:2 ratio) (Fechner and others ) or pea protein with pectin (1:3 ratio) (Tamnak and others ), and the acidic precipitation of coacervates of whey protein concentrate with polysaccharides (Jiménez‐Alvarado and others ). These mixed biopolymer‐based conjugates and coacervates can be used as hydrophilic emulsifying agents in the W2 phase of W1/O/W2 systems in order to enhance the stabilizing characteristics of the outer oil–water interface.…”
Section: Preparation Of Double Emulsionsmentioning
confidence: 99%